The man swimming against the stream knows the strength of it: hydraulics and social relations in an Argentinean irrigation system - Ertsen, Maurits W., author; van Nooijen, Ronald, author; van Son, Bas, author; U.S. Committee on Irrigation and Drainage, publisher (Colorado State University. Libraries, 2007)
In this paper we discuss hydraulic behavior of irrigation infrastructure within a context of spatially distributed power relations in an Argentinean irrigation system. In the Río Dulce basin the irrigation area known as the Proyecto Río Dulce (PRD, command area 350,000 hectares) is the main irrigated area. An interesting characteristic of the PRD is that the larger landowners are mainly situated in tail end areas. Despite this potentially disadvantageous position, downstream farmers do not encounter problems. This should not be regarded as self-evident: the hydraulic properties of the canals induce a need for downstream farmers to take deliberate action to ensure proper water delivery to their farms. When upstream farmers do not irrigate, too much water can flow downstream; when they irrigate too much, or manipulate cross regulators, downstream water scarcity can be the result; when canals are not maintained, extensive plant growth will increase hydraulic resistance and decrease discharges. It is not a coincidence that the downstream farmers invest heavily in canal maintenance. These investments appear to be appropriate, as larger farmers tend to irrigate much more on average compared to the smaller farmers upstream.
USCID fourth international conference
Hydraulics and social relations in an Argentinean irrigation system
Not digitized by CSUL Digital Services.
Presented at the Role of irrigation and drainage in a sustainable future: USCID fourth international conference on irrigation and drainage on October 3-6, 2007 in Sacramento, California.